Sustaining tank irrigation in South India through time-tested measures - Kuppannan, Palanisami; Thangavel, M. (2021)
The century old irrigation tanks mostly found in south India account for about 1/3 of rice irrigated areas and largely benefit the small and marginal farmers. The current performance of these tanks is below the 50 percent level. Major factors contributing to their declining performance are: erratic rainfall pattern and reduced inflows (hydrology side); poor management of the tanks (tank side); ineffective water control & poor groundwater development (farmers’ side). Given the future impacts of climate change on water resources, sustaining tank irrigation is considered important. Evidence shows that developing an interface between tank ecosystems and wells is expected to augment water supplies, improve tank management and boost tank irrigation. This paper outlines a five-pronged strategy to achieve this: a) partial rehabilitation (partial desilting); b) full scale tank rehabilitation; c) converting tanks into percolation ponds; d) converting non-system tanks into system tanks; e) full scale groundwater development (tapping the full groundwater potential). Financial viability of the strategy also varies according to the scale and size of the investments and the expected benefits. There is an important need for policy reforms converging ongoing as well as proposed programs (by national and international funding agencies) on tank rehabilitation; these can be planned in a phased manner by prioritizing the investment scenarios.